Maternal investment mediates offspring life history variation with context‐dependent fitness consequences. Issue 9 (1st September 2015) - Moore, Michael P.; Landberg, Tobias; Whiteman, Howard H.
Abstract : Maternal effects, such as per capita maternal investment, often interact with environmental conditions to strongly affect traits expressed early in ontogeny. However, their impact on adult life history traits and fitness components is relatively unknown. Theory predicts that lower per capita maternal investment will have strong fitness costs when the offspring develop in unfavorable conditions, yet few studies have experimentally manipulated per capita maternal investment and followed offspring through adulthood. We used a surgical embryonic yolk removal technique to investigate how per capita maternal investment interacted with an important ecological factor, larval density, to mediate offspring life history traits through reproductive maturity in an amphibian, Ambystoma talpoideum . We predicted that increased larval density would reinforce the life history variation induced by differences in per capita investment (i.e., Controls vs. Reduced Yolk), with Reduced larvae ultimately expressing traits associated with lower fitness than Controls when raised at high densities. We found that Reduced individuals were initially smaller and more developed, caught up in size to Controls within the first month of the larval stage, but were smaller at the end of the larval stage in low densities. Reduced individuals also were more likely to undergo metamorphosis at high densities and mature females invested in more eggs for their body sizes than Controls. Together, our results do not support our hypothesis, but instead indicate that Reduced individuals express traits associated with higher fitness when they develop in high‐density environments, but lower fitness in low‐density environments. The observed life history and fitness patterns are consistent with the "maternal match" hypothesis, which predicts that when the maternal environment (e.g., high density) results in phenotypic variation that is transmitted to the offspring (e.g., reduced per capita yolk investment), and offspring face that same environment (e.g., high larval density), the fitness of both mother and offspring is maximized.